An Assessment of the Socio-Economic Status of Bargur Buffalo Farmers in the Native Tract (Indian Journal of Animal Production and Management, 2025)
The present study was undertaken to analyze the socio-economic  characteristics of Bargur buffalo farmers in their native tract. Data were  collected from 100 selected respondents using a pre-tested and structured  interview schedule over five months. The results revealed that most of the  respondents were female (57%), highlighting the significant role of women  in buffalo-rearing activities. Most farmers were middle-aged or elderly (87%)  and belonged to nuclear family structures (57%). A large proportion (88%)  were from the Backward Class and possessed marginal landholdings (83%).  Regarding educational status, 61% had primary education, and 40% were  illiterate. Agriculture was the primary occupation for 97% of the respondents,  and the annual income of most farmers ranged from low to moderate income.  Livestock ownership was generally small, with 58% of farmers maintaining  three to five buffaloes each. Notably, 76% of the respondents had more than  10 years of experience in buffalo rearing, reflecting the traditional nature  of the occupation. However, none of the respondents had received formal  training in buffalo management or husbandry. These findings emphasize the  need for targeted capacity-building programs and strengthened extension  services to enhance productivity and ensure livelihood security among  farmers.
Keywords: Socio-economic profile; Buffalo farming; Bargur buffalo; Tamil Nadu